Giving Vernonia Amygdalina Juice to Cholesterol, Uric Acid, and Blood Glucose in Broiler Chickens - Syamsuddin Syamsuddin; Deki Zulkarnain; Nasriati Nasriati; Rusli Badaruddin; Amiluddin Indi (Journal of Tropical Animal Science and Technology, 2022)
The aim of the study was to examine the effect of giving African leaf juice (Vernonia amygdalina) on cholesterol, uric acid and blood glucose of broiler chickens. The research was carried out in August-September 2021 at the broiler chicken coop unit of the Poultry Livestock Unit Laboratory, Faculty of Animal Science, Halu Oleo University, Kendari. The research method used was a completely randomized design (CRD) using 100 broiler DOCs with 4 treatments and 4 replications and there were 16 experimental units. The treatments used in this study were P0 = without African leaf juice (control), P1 = 2cc of African leaf juice/1 liter of water in drinking water, P2 = 4cc of African leaf juice/1 liter of water in drinking water, P3 = 6cc of African leaf juice /1 liter of water in drinking water. The variables observed were cholesterol, uric acid and blood glucose. The results of the study showed that administration of African leaf juice with levels of 2cc, 4cc, 6cc had no effect (P>0,05) on cholesterol, uric acid and blood glucose of broiler chickens. Thus, it was concluded that the administration of African leaf juice had no effect on cholesterol, uric acid and blood glucose of broiler chickens.